2010
DOI: 10.1016/j.yjmcc.2009.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Investigations into tropomyosin function using mouse models

Abstract: Tropomyosin plays a key role in controlling calcium regulated sarcomeric contraction through its interactions with actin and the troponin complex. The focus of this review is on striated muscle tropomyosin isoforms and the in vivo approach we have taken to define the functional differences among these isoforms in regulating cardiac physiology. In addition, we address specific regions within tropomyosin that differ among the isoforms to impart differences in the physiological performance of muscle and the sarco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 44 publications
4
51
0
Order By: Relevance
“…They reported that Tm- is associated with a slowing of relaxation and an increase in the Ca 2+ -sensitivity of force generation compared with control myocardium, which expresses predominantly fast-type Tm-a. Slowtype Tm-a increases isometric contraction and relaxation rates and decreases Ca 2+ -sensitivity in transgenic mouse hearts (Jagatheesan et al, 2010). Our results show that the jaw-closing muscles of members of Carnivora express little or no Tm-, which suggests that contractions could be faster and that the Ca 2+ -sensitivity of force generation would be lower.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…They reported that Tm- is associated with a slowing of relaxation and an increase in the Ca 2+ -sensitivity of force generation compared with control myocardium, which expresses predominantly fast-type Tm-a. Slowtype Tm-a increases isometric contraction and relaxation rates and decreases Ca 2+ -sensitivity in transgenic mouse hearts (Jagatheesan et al, 2010). Our results show that the jaw-closing muscles of members of Carnivora express little or no Tm-, which suggests that contractions could be faster and that the Ca 2+ -sensitivity of force generation would be lower.…”
Section: Discussionmentioning
confidence: 66%
“…At least four genes encode the Tm isoforms that are expressed in skeletal and cardiac muscles (reviewed in Perry, 2001;Gunning et al, 2005;Jagatheesan et al, 2010) and one gene codes for multiple fast-type TnT isoforms in vertebrate skeletal muscle (Medford et al, 1984;Wilkinson et al, 1984;Breitbart et al, 1985;Hastings et al, 1985). The expression of these proteins is regulated by extensive alternative RNA splicing, which has the potential to yield complex patterns between muscles of a given organism or even between individual fibers within a specific muscle (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To compensate for this increased calcium sensitivity, we generated a double-transgenic mouse expressing a chimeric Tm containing the α-Tm amino terminus and the carboxyl terminus of β-Tm, the fetal cardiac isoform (Chi 1) (30). Previous work demonstrated that myofilaments from these Chi 1 mice have a decreased sensitivity to calcium (33,34). The double-transgenic mice which were created by crossing the 2 lines displayed normalized myofilament calcium sensitivity.…”
Section: Rescue Of Cardiomyopathic Mice By Contractile Proteinsmentioning
confidence: 99%